Rational design of triphenylamine dyes for highly efficient p-type dye sensitized solar cells - Zhu, Linna (2016)
Two new sensitizers based on triphenylamine-dicyanovinylene have been synthesized and used for p-type dye-sensitized solar cells. The best performance amongst solar cells was achieved by the dye with a ter-thiophene bridge ligand between carboxylic acid group and the triphenylamine part (with power conversion efficiency of 0.19%, short circuit current of 4.01 mA cm−2, open circuit voltage at 144 mV, and fill factor of 0.33). Results indicate that the ter-thiophene groups in the dyes strongly affects both charge recombination and hole injection in the photoelectrode. In addition, the hexyl chains on the bridged thiophene rings also help to avoid dye aggregation on the nickel oxide film and block I− in electrolyte from approaching the surface of nickel oxide, which leads to a reduction in the charge recombination between nickel oxide semiconductor and electrolyte. This study suggested that modification of the bridge moiety between triphenylamine and the carboxylic group by increasing thiophene units is a promising way for preventing charge recombination and increasing the power conversion efficiency.